A Facile Magnetic Extrusion Method for Preparing Endosome‐Derived Vesicles for Cancer Drug Delivery. (20th January 2021) - Guo, Peng; Busatto, Sara; Huang, Jing; Morad, Golnaz; Moses, Marsha A.
Abstract: To date, the scaled‐up manufacturing and efficient drug loading of exosomes are two existing challenges limiting the clinical translation of exosome‐based drug delivery. Herein, a facile magnetic extrusion method is developed for preparing endosome‐derived vesicles, also known as exosome mimetics (EMs), which share the same biological origin and similar morphology, composition, and biofunctions with native exosomes. The high yield and consistency of this magnetic extrusion method help to overcome the manufacturing bottleneck in exosome research. Moreover, the proposed standardized multi‐step method readily facilitates the ammonium sulfate gradient approach to actively load chemodrugs such as doxorubicin into EMs. The engineered EMs developed and tested here exhibit comparable drug delivery properties as do native exosomes, and potently inhibit tumor growth by delivering doxorubicin in an orthotopic breast tumor model. These findings demonstrate that EMs can be prepared in a facile and scaled‐up manner as a promising biological nanomedicine for cancer drug delivery. Abstract : A magnetic extrusion method is developed to prepare endosome‐derived vesicles, also called exosome mimetics (EMs), in a facile and scaled‐up manner. The engineered EMs share the same biological origin and similar morphology, composition, and biofunctions with native exosomes, which can be utilized as a promising biological nanomedicine for cancer drug delivery.